The use of ultrasound to assess fetal growth in a guinea pig model of fetal growth restriction. (April 2017) - Swanson, A M; Mehta, V; Ofir, K; Rowe, M; Rossi, C; Ginsberg, Y; Griffin, H; Barker, H; White, T; Boyd, M; David, A L
Fetal growth restriction (FGR) is a common and potentially severe pregnancy complication. Currently there is no treatment available. The guinea pig is an attractive model of human pregnancy as placentation is morphologically very similar between the species. Nutrient restriction of the dam creates growth-restricted fetuses while leaving an intact uteroplacental circulation, vital for evaluating novel therapies for FGR. Growth-restricted fetuses were generated by feeding Dunkin Hartley guinea pig dams 70% of ad libitum intake from four weeks before and throughout pregnancy. The effect of maternal nutrient restriction (MNR) on dams and fetuses was carefully monitored, and ultrasound measurements of pups collected. There was no difference in maternal weight at conception, however by five weeks post conception MNR dams were significantly lighter ( P  < 0.05). MNR resulted in significantly smaller pup size from 0.6–0.66 gestation. Ultrasound is a powerful non-invasive tool for assessing the effect of therapeutic interventions on fetal growth, allowing longitudinal measurement of fetuses. This model and method yield data applicable to the human condition without the need for animal sacrifice and will be useful in the translation of therapies for FGR into the clinic.